Effect of Beta-Mannanase Supplementation on Growth Performance, Fecal Consistency, and Carcass Characteristics of Weanling Pigs - Mariel Rebosura; Listya Purnamasari; Joseph Flores dela Cruz; Seong Gu Hwang (Buletin Peternakan, 2023)
The study aimed to investigate the effect of beta-mannanase supplementation on growth performance, fecal consistency, and carcass characteristics of weanling pigs. A total of 100 weaned piglets (initial body weight = 7 ± 0.5 kg) were divided into 2 dietary treatments of (T1) control diet; and (T2) beta-mannanase supplemented diet. Each treatment was replicated 5 times with a pen of 10 piglets each following a completely randomized design. Feed and water were supplied ad libitum during the 30- day feeding trial. Fecal scores per pen were determined every morning on a daily basis; 1 pig per replicate was randomly selected for carcass evaluation. The results showed that there were no significant differences (P>0.05) in feed conversion ratio, fecal consistency scores, dressing percentage, and loin eye area between T1 and T2. Treatment T1 produced a greater body weight and gained weight faster compared to T2. In conclusion, beta-mannanase supplementation did not improve growth performance, fecal consistency, and carcass characteristics in weanling pigs. The amount of beta-mannanase was not enough to degrade the non-starch polysaccharides of the soybean meal.